Determinant of Foreign Exchange Reserve in 6 Asian Developing Country Before and During Crisis Pandemic COVID-19 - Khoirunnisa, Annis; Oktavilia, Shanty (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339)DO - 10.24843/JEKT.2022.v15.i02.p03, 2022)
This research looks at the factors that affect foreign exchange reserves in developing countries in Asia 6 in the period before and during the crisis due to the covid-19 pandemic. Used panel data regression estimates, which are a combination of time series data (Q1 2018-Q4 2020) and cross sections (India, Indonesia, Philippines, Thailand, Mongolia, and Uzbekistan). The variables used are foreign exchange reserves as the dependent variable then exchange rate, GDP, FDI, net exports, the period before and during the crisis (dummy) as independent variables. The results of this study are partially variable exchange rate, GDP, FDI, net exports have a significant positive effect on foreign exchange reserves. The period before and during crisis (dummy) have a different effect on foreign exchange reserves. Keywords : Foreign Exchange Reserves, Developing Countries, Pandemic COVID-19, Panel. Classification JEL: F31, O1, C33